Minions [videorecording (DVD)] (Universal Studios Home Entertainment, 2015)
Minions evolve through the ages, perpetually serving the most despicable of masters--which they are continuously unsuccessful at keeping. One Minion named Kevin, however, has a plan, and he and two of his Minions cohorts venture out into the world to find a new evil boss for his brethren to follow.